Composite pipes subjected to bending loads - Lim, Seok Hee. (2010)
The aim of this project is to investigate and analyse the deformation and strain experience by the pipe when subjected to bending. This involves fabrication of support, mounting of strain gauges, experimental and software investigation of the behavior under bending.